Pengaruh Asimetri Informasi dan Ukuran Perusahaan terhadap Manajemen Laba pada Sub Sektor Industri Rokok yang Terdaftar di Bursa Efek Indonesia Periode 2013-2017 - Esty Rohayati (Universitas Batanghari Jambi, 2019)
Earnings management as a phenomenon is influenced by various kinds of factors that are the drivers of the emergence of this phenomenon. Information asymmetry and firm size are believed to influence earnings management. Several studies on the effect of information asymmetry and firm size on earnings management have been carried out. However, the results obtained still show inconsistencies, especially the size of the company. In this study, earnings management was measured by The modified Jones Model to calculate discretionary accruals. Information asymmetry is measured using bid-ask and the size of the company is measured using total assets. The study population consisted of 4 companies and the observation period starting in 2013-2017. The data used in this study are secondary data and sample selection using the purposive sampling method. Based on the results of the purposive sampling obtained 4 companies in the cigarette sector that met the sample criteria. The analytical method used is a multiple linear analysis method to test the effect of information asymmetry and firm size on earnings management. Statistical analysis is used, namely 1. Testing classic assumptions, which consist of normality test, heterocedasticity test, multicollinearity test and autocorrelation test. 2. Testing the hypothesis, which consists of a test of the coefficient of determination (R2), partial hypothesis testing (t-test) and simultaneous hypothesis testing (F-test). Based on the results of hypothesis testing using multiple linear analysis in this research, it can be concluded partially that information asymmetry has a positive and significant effect on earnings management, while firm size has a positive and significant effect on earnings management. As well as simultaneous testing, it was concluded that information asymmetry and company size had a positive and significant effect on earnings management in 4 (four) companies, Cigarette Industry Sub-Sector Registered on the Indonesia Stock Exchange (IDX). From the results of testing the coefficient of determination or (R Square) from the results of the second regression the independent variable (Information Asymmetry and Company Size) on Earnings Management is 99.0%, so based on the research results 99.0% (100-99.0) and the rest 1,0% is influenced by other factors not examined in the study.